Análisis de la efectividad de la revisión de los estándares mínimos en la disminución de las tasas de accidentalidad y enfermedad laboral en las empresas. - Sánchez Calvete, Juan Sebastián; Medina Santana, Mayra Alejandra (Corporación Universitaria Minuto de Dios - UNIMINUTO, 2022)
La investigación documental consistió en analizar los estándares mínimos en la disminución de las tasas de accidentalidad y enfermedad laboral en las empresas para lo cual se formularon 3 objetivos como identificar datos estadísticos de accidentalidad y enfermedad laboral de cinco empresas, determinar el nivel de cumplimiento de los estándares mínimos y por último correlacionar el cumplimiento de estándares mínimos versus tasa de accidentalidad.

The documentary research consisted of analyzing the minimum standards in the reduction of the rates of accidents and work-related illnesses in companies, for which 3 objectives were formulated, such as identifying statistical data on accidents and work-related illnesses of five companies, determining the level of compliance with the minimum standards and, finally, to correlate compliance with minimum standards versus the rate of accidents and work-related illnesses. Once the investigation was completed, it was possible to determine that compliance with the minimum standards is not effective in reducing accident rates and workrelated illnesses, since these depend on multiple factors such as working conditions, awareness, self-care and existing controls in organizations.
Keywords: Accidente de trabajo; Enfermedad laboral; Estándares mínimos; FASECOLDA; Datos estadísticos.; Work accident; Occupational disease; Minimum standards; FASECOLDA; Correlation; Statistical data